2014
DOI: 10.1002/jctb.4559
|View full text |Cite
|
Sign up to set email alerts
|

Biodesulfurization of dibenzothiophene by resting cells of Pseudomonas putidaCECT5279: influence of the oxygen transfer rate in the scale‐up from shaken flask to stirred tank reactor

Abstract: BACKGROUND In this work, the scale‐up of the biodesulfurization process at rest from shaken flask to stirred tank bioreactor cells has been studied taking into account the influence of the hydrodynamic conditions of the oxygen transfer rate. RESULTS Different hydrodynamic conditions to carry out the biodesulfurization in a stirred tank bioreactor have been studied and compared with the results obtained in a shaken flask. The best results were obtained at a stirrer speed of 400 rpm and an air flow rate of 2 vvm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 34 publications
(59 reference statements)
2
13
0
Order By: Relevance
“…Since DBT is not present in the cultures, and thus the 4S route is inoperative during the cultures, the experimental observations in GMO strains under low agitation conditions are not derived by the activity of the enzymes encoded in plasmid pESOX3. It has been reported that the presence of DBT reduces the toxicity of hydrogen peroxide, due to the performance of the 4S route in resting cells . Similar effects derived of the presence of H 2 O 2 in Pseudomonas cultures have been previously reported .…”
Section: Resultssupporting
confidence: 77%
See 3 more Smart Citations
“…Since DBT is not present in the cultures, and thus the 4S route is inoperative during the cultures, the experimental observations in GMO strains under low agitation conditions are not derived by the activity of the enzymes encoded in plasmid pESOX3. It has been reported that the presence of DBT reduces the toxicity of hydrogen peroxide, due to the performance of the 4S route in resting cells . Similar effects derived of the presence of H 2 O 2 in Pseudomonas cultures have been previously reported .…”
Section: Resultssupporting
confidence: 77%
“…In the experiments carried out with the strain KTH2 (pESOX3), 0.025 g L −1 of tetracycline have to be added into LB or BSM medium, to prevent the loss of the operon dszABC ‐containing plasmid. The induction of the plasmid‐encoded genes was accomplished by adding 2 × 10 −6 g L −1 of IPTG before STBR inoculation …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…at 30°C [21]. Martinez et al [22] studied the biodesulfurization of dibenzothiophene by resting cells of Pseudomonas putida CECT5279, where complete conversion into HBP was reached in 90 min, using a gas flow of 2 vvm, thus…”
Section: Discussionmentioning
confidence: 99%